1998
DOI: 10.1023/a:1005840420136
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have analyzed expression of a receptor protein tyrosine phosphatase (RPTPzeta/beta) in tissue samples from 23 human gliomas. Using the reverse transcription-polymerase chain reaction (RT-PCR) technique, we assayed for the presence or absence of mRNA transcripts encoding the intact receptor and 2 alternatively spliced forms of RPTPzeta/beta. Transcripts encoding the intact and truncated receptors were expressed in all of the lower grade gliomas (WHO grade 1-3) analyzed, but not in 55% of the grade 4 glioblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…According to previous descriptions and as shown for each set schematically, these primer pairs bind to specific regions of the three RPTPβ/ζ isoforms ( Figure 2 A; [ 45 ]). The glioblastoma multiforme cell line U-251 served as positive control, since all RPTPβ/ζ isoforms are prominently expressed in different grades of glioma types [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous descriptions and as shown for each set schematically, these primer pairs bind to specific regions of the three RPTPβ/ζ isoforms ( Figure 2 A; [ 45 ]). The glioblastoma multiforme cell line U-251 served as positive control, since all RPTPβ/ζ isoforms are prominently expressed in different grades of glioma types [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…By combining different primer pairs, modified according to Norman et al, unique RPTPβ/ζ (PTPRZ1) isoforms were analyzed via semi-quantitative RT-PCR ( Table 2 ) [ 45 ]. RT-PCR using CP and EC primer pairs was performed with Taq DNA Polymerase (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motile glioma cells can remodel this matrix by local degradation of ECM molecules and synthesis of a novel pericellular scaffold (11). The glioma ECM contains molecules that predominate during neural development (hyaluronic acid, phosphacan, SPARC) (14, 15), mesenchymal proteins found in peripheral stroma and basal lamina (collagens, fibronectin) (16), and chondroitin sulfate proteoglycans that limit cell motility in the adult CNS (versican, brevican) (17, 18) but instead promote glioma cell migration (7, 19, 20). Recent evidence from our and other laboratories has suggested that the presence of both mesenchymal and neural-specific matrix proteins in gliomas may result in novel molecular interactions that specifically promote glioma cell motility in the CNS (19, 21).…”
mentioning
confidence: 99%
“…Among these genes we find several known to be associated with cancers. PTPRT , a protein tyrosine phosphatase receptor, is a signaling molecule known to be implicated in oncogenic transformation in several different cancers 13 , including colon cancer 14,15 , glioma 16 , and melanoma 17 . NELL1 and NELL2 , growth factor like protein thought to be involved in regulation of cell growth, has also been associated with multiple cancer types, including esophageal adenocarcinoma 18 , colon cancer and Burkitt’s lymphoma 19 .…”
Section: Discussionmentioning
confidence: 99%